Emerging Technological Trends in Financial Crime and Money Laundering: A Bibliometric Analysis of Cryptocurrency's Role and Global Research Collaboration - Pramanik, Md Ileas; Ghose, Provakar; Hossen, Md. Deluar; Ahmed, Mohammad Helal Uddin; Rahman, Md. Mahfuzur; Bhuiyan, Mohammad Rakibul Islam (Journal of Posthumanism, 2025)
This study explores financial crime and money laundering trends through a bibliometric analysis using Scopus and Web of Science databases. The primary objective is to assess research themes, scholarly contributions, and emerging topics in financial crime and money laundering, particularly those involving cryptocurrency. The methodology involves a comprehensive data collection process, with 1280 articles screened using inclusion and exclusion criteria, narrowing to 190 articles for in-depth analysis. Tools like VOSviewer, MS Excel, and Biblioshiny R package were employed for bibliometric coupling, keyword co-occurrence, and thematic clustering. Findings reveal the central role of cryptocurrency in financial crimes, with specific attention to techniques like fraud detection, cybercrime, and anti-money laundering. It highlights the rapid increase in publications since 2017, attributed to cryptocurrency adoption, regulatory developments, and the prevalence of financial crime. The USA, UK, and Australia emerged as major contributors, with the USA displaying the highest collaborative research efforts. Practical implications are significant for policymakers, offering insights to enhance digital transfer security and inform measures against money laundering risks. The study's social implications underline the need for robust cybersecurity and forensic measures to combat online financial crimes effectively. Limitations include its reliance on English-language documents and focus on specific publication databases, and generalizability. Future research directions suggest further investigation into cryptocurrency’s psychological impacts, consumer trust, and geographical distribution of fraud activities. This study's originality lies in its bibliometric approach, combining quantitative and qualitative insights, filling research gaps on emerging digital financial crime trends, especially related to cryptocurrency and global collaborative research.